STUDY OF THE POTENTIAL OF BALOHAN VILLAGE, SUKAJAYA DISTRICT, SABANG CITY AS AGRO-TOURISM - Nur Intan Simangunsong; Rini Fitri; Reza Fauzi (Journal of Synergy Landscape, 2022)
The city of Sabang is one of the national and foreign tourist destinations because of thebeauty of the natural panorama and the available infrastructure. Weh Island is also blessedwith agricultural resources so that it has the potential to be developed into an agro-tourismarea. The potential of agro-tourism in Sabang City has not been fully developed and utilizedoptimally. The purpose of this study is to identify and analyze physical, biophysicalconditions including facilities, social, economic, and cultural as well as providerecommendations to be developed into agro-tourism. This research was conductedqualitatively and exploratory in nature, using a case study approach. Data collectiontechniques for inventorying physical, social data from sites and infrastructure usingobservation methods equipped with data recording instruments (cameras) to obtaininformation about agro-tourism. Descriptive data analysis and the analysis results obtainedrelated to agro-tourism potential were also analyzed using SWOT (Strenghts, Opportunities,Weaknesses and Threats) analysis. The results showed that Sukajaya District could bedeveloped into agro-tourism because it has the potential of various fruit orchards,horticultural gardens and vegetable gardens. It is necessary to provide educational tourismprograms, recreation, and economic tourism so that they are sustainable by taking intoaccount the ecological system, economic growth, and local socio-cultural.